Alteration of swallowing in the elderly after cerebrovascular accident: An integrative review study - Chaves, Simone Pereira Lins (2021)
Objective: Identify the alterations of swallowing in the elderly after cerebrovascular accident in scientific productions. Methods: Integrative literature review performed on the following databases: Lilacs, Scielo, Pubmed Medline and Science Direct. Results: The studies evidenced several alterations, categorized as alimentary, pulmonary, nutritional, functional alterations and effects on quality of life. Conclusion: There stands out the importance of new researches on the theme, evidencing the importance of an effective targeting by health professionals of these people to an integral and multidisciplinary assistance, to the speech therapy professional and to the multidisciplinary team.